Self-regulatory and metacognitive instruction regarding student conceptions: influence on students’ self-efficacy and cognitive load - Hartelt, Tim; Martens, Helge (Frontiers in Psychology, 2024)
Self-regulatory and metacognitive instruction regarding student conceptions can help students become metacognitively (or more specifically, metaconceptually) aware of their conceptions and self-regulate their intuitive conceptions in scientific contexts when they are not appropriate. Two approaches have been found effective in enhancing conceptual knowledge: (a) self-assessing one's conceptions and (b) acquiring conditional metaconceptual knowledge about why and in which contexts specific conceptions are appropriate or not. However, it is unclear how these approaches influence other cognitive and affective variables, such as self-efficacy and cognitive load.Nevertheless, it is essential to investigate whether making students aware of their intuitive conceptions affects their self-efficacy and to what extent reflecting on one's conceptions requires additional (meta-)cognitive resources. Thus, we conducted an experimental intervention study using a 2x2 factorial design with N = 602 upper secondary biology students. Becoming metaconceptually aware of one's (intuitive) conceptions did not lower students' self-efficacy but enabled more accurate beliefs about their abilities. However, the self-assessment increased mental load, which partly suppressed the beneficial effect of the self-assessment on conceptual knowledge.In contrast, the instruction on conditional metaconceptual knowledge did not result in higher mental load and, thus, aligned more with students' cognitive capacities. Furthermore, students with more pronounced general metaconceptual thinking reported lower mental load, implying that regular instruction focusing on metaconceptual thinking may reduce load. Thus, it is suggested to continuously promote students' metaconceptual thinking and to embed metaconceptual activities (e.g., self-assessments) repeatedly across longer instructional units.